Pacitan dalam Pembangunan Masa Bupati Sutjipto Tahun 1998 – 2000: Suatu Tinjauan Historis Peraturan Daerah - Nurul Hidayat; Heru Arif Pianto (Jurnal Siginjai, 2021)
This study aims to determine the history of government and bureaucracy after the fall of President Soeharto's government which was arranged during the crisis. The history of the government in question is the government in Pacitan Regency which at that time coincided with the reign of the Sitjipto Regent. At that time, almost all regions throughout the archipelago felt the impact, especially in the field of development. The research uses the historical method by reconstructing the past through a process of critical testing and analysis of the records and relics of the past. Broadly speaking, historical research includes four steps, starting from heuristics (collection of sources), criticism (verification), interpretation (imagination based on facts), and historiography (arranging facts chronologically). During the reign of Regent Sutjipto, in the period 1998-2000 he carried out a five-year development plan which was approved by the previous government through Perda no. 1 1994 concerning Basic Patterns of Pacitan Level II Regional Development 1994/1995 – 1998/1999. With a focus on the development of human and economic resources. Even with the crisis situation, Pacitan was able to adapt and the results werebased on the Susenas survey with several indicators, Pacitan experienced an increase in population and population growth, sex ratio, number of households, and population density.